2016
DOI: 10.1186/s12913-016-1899-z
|View full text |Cite|
|
Sign up to set email alerts
|

The potential effectiveness of the nutrition improvement program on infant and young child feeding and nutritional status in the Northwest and Southwest regions of Cameroon, Central Africa

Abstract: BackgroundDespite the recent international focus on maternal and child nutrition, little attention is paid to nutrition capacity development. Although infant feeding counselling by health workers increases caregivers’ knowledge, and improves breastfeeding, complementary feeding, and children’s linear growth, most of the counselling in sub-Saharan Africa is primarily conducted by nurses or volunteers, and little is done to develop capacity for nutrition at the professional, organizational, or systemic levels. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
12
0
3
Order By: Relevance
“…Furthermore, higher number of children from the intervention areas fulfilled minimum dietary diversity requirement of eating food items from at least 4 food groups, which is particularly important for the children to attain proper nutrition [41, 42]. A few studies [16, 17] carried out in similar settings also reported that counselling mothers on child feeding practices is associated with overall improvement in optimum infant and child feeding practices. Although, some studies found that maternal nutrition counselling results in reduced childhood stunting [19, 20], other studies [43, 44] reported that nutrition counselling were ineffective in reduction of stunting among young children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, higher number of children from the intervention areas fulfilled minimum dietary diversity requirement of eating food items from at least 4 food groups, which is particularly important for the children to attain proper nutrition [41, 42]. A few studies [16, 17] carried out in similar settings also reported that counselling mothers on child feeding practices is associated with overall improvement in optimum infant and child feeding practices. Although, some studies found that maternal nutrition counselling results in reduced childhood stunting [19, 20], other studies [43, 44] reported that nutrition counselling were ineffective in reduction of stunting among young children.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, suboptimal feeding practices in childhood has been identified as one the most three prominent drivers of childhood stunting in South Asian countries [15]. Although some studies carried out in resource poor setting reported that maternal nutrition counselling is associated with improved infant and young child feeding (IYCF) practices [16, 17] and reduced childhood stunting [1820], there is limited evidence from Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of maternal health and nutrition, these include: maternal nutritional and health status before, during and after pregnancy that influences a child's early growth and development, commencement in the womb. Infant and young child feeding practices that contribute to stunting include suboptimal breastfeeding (specifically, non-exclusive breastfeeding) and balancing feeding that is limited in quantity, quality and variety [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Hence,interventions in the form of nutritional counselling services and health educational talks that are offered to caregivers with children below two years have been recommended as effective strategies that can help improve infant and young child feeding (IYCF) practices, reduce child undernutrition and hence enhance child survival [9, 12, 13]. However, Reinsma et al, (2016) [14] noted that although most of the nutrition counselling in sub-Saharan Africa is primarily conducted by nurses or health volunteers, little is done to develop capacity for nutrition at the professional, organizational, or systemic levels. In addition, Kohli and Chadha (2017) [12] asserted that, studies that focus on assessing nutritional counselling activities and skills of health workers are scarce.…”
Section: Introductionmentioning
confidence: 99%